The Short-Term Impact of Product Market Reforms : A cross-country firm-level analysis - Gal, Peter; Hijzen, Alexander (Washington, D.C. : International Monetary Fund, 2016)
This paper analyzes the effects of product market reforms in the short and medium term across 10 regulated industries and 18 advanced economies for the period 1998-2013 using internationally comparable firm-level data based on Orbis. It provides four key insights. First, product market reforms have positive effects on capital, output and employment and their effects increase over time. After two years, they raise capital by 4%, output by 3% and employment by 1.5%. Second, differences in production technology and the nature of product market regulations across sectors generate important differences in the mechanisms through which reforms operate. In network industries, reforms tend to benefit small firms, while the opposite is observed in retail trade. Product market reforms also promote firm entry, particularly those that reduce entry barriers. Third, credit constraints can play an important role in weakening the positive impact of product market reform on investment. Fourth, product market reforms also tend to have positive effects on firms in downstream sectors-both at home and abroad-that make intensive use of intermediate inputs from deregulated sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet